S144 Quality Of Life In Idiopathic Pulmonary Arterial Hypertension Is Associated With Quadriceps Function And Size. (10th November 2014) - Garfield, BE; Parfitt, L; Harries, C; Dimopoulos, K; Gatzoulis, M; Kemp, P; Polkey, MI; Wort, SJ
Abstract : Introduction: Despite recent improvements in therapy patients with idiopathic pulmonary arterial hypertension (IPAH) still suffer with significantly reduced quality of life (QOL). Muscle dysfunction and low physical activity are emerging as important complications of the disease. Separately rehabilitation programs have been shown to cause an improvement in both QOL and muscle strength but the direct relationship between these factors has not as yet been documented in this condition. Aims: We aimed to define the relationship between QOL and muscle function, size and physical activity in patients with IPAH. Methods: In 12 patients with IPAH we measured quadriceps maximal volitional capacity (QMVC), ultrasound cross sectional area of the rectus femoris (USRF CSA), fat free mass index by bioelectrical impedance (FFMI), physical activity using the Sensewear armband (steps per day, total energy expenditure (TEE), and active energy expenditure (AEE)). They were also asked to complete the St. George's respiratory questionnaire (SGRQ). Correlations were performed with Pearson's or Spearman's test. Results: In the 12 patients with data so far available in this study QOL measured by the total SGRQ score correlated significantly with QMVC/BMI (r = -0.75, p = 0.005), FFMI (r = -0.71, p = 0.009) and USRFCSA (r = -0.88, p = 0.0002) (Figure 1A ). There was no significant correlation between total SGRQ score and Sensewear measured steps per day (r = -0.62, p = 0.08) (Figure 1B ) TEE (r = -0.62, p = 0.08) or AEE (rho = -0.41, p > 0.05) in the 9 patients with data available. Furthermore there was no significant correlation between BNP or resting echocardiographic parameters and total SGRQ QOL Discussion: We have shown that muscle size and function are directly related to QOL in patients with IPAH. This work suggests that muscle function may be an important determinant of QOL in these patients, making it a potential target for therapeutic intervention. Further data is needed to define the association between physical activity and QOL in patients with IPAH.